A intervenção humanitária e a (in)decisão soberana - Silva, Henrique Candido da (2015)
The background to this paper is the challenging field of the human security, where the objects of reference are the State and the sovereign decision; and the main issue is the use of emergency measures, such as the humanitarian intervention. The aim of this paper is to contribute to the discussion about the priority between the safety of States or of human beings, especially when it comes to the paradox of the defence of Human Rights through force, or, in other words, protection of life through the production of death. In order to do so, the ontogenetic analysis of the state of exception will be employed, showing that the permission to the use of force, concretized through the humanitarian intervention, exposes man s humanity to something that can, simultaneously, save it and destroy it, constituting an autoimmune malfunction of the Law s autopoietic system. Our conclusion, therefore, is that the sedimentation of the idea of prevention in the global community is the most appropriate element to the safeguard of the Human Rights, and that the considerations on the legitimacy of humanitarian intervention prove themselves to be useless, be it because they constitute an immunizer instrument that searches its legitimation in the inclusion of life through its suspension, be it because it constitutes a pretentiously juridical action occurring in an anomic field where the corpus won the battle against the free man